2022
DOI: 10.1007/s00702-022-02541-1
|View full text |Cite
|
Sign up to set email alerts
|

Potentially inappropriate medications according to PRISCUS list and FORTA (Fit fOR The Aged) classification in geriatric psychiatry: a cross-sectional study

Abstract: Adverse drug reactions (ADRs) constitute a frequent cause of hospitalization in older people. The risk of ADRs is increased by the prescription of potentially inappropriate medications for older people (PIMs). The PRISCUS list and the FORTA classification represent established tools to detect PIMs. The aim of the present study was to examine the prevalence and characteristics of PIM prescriptions on the gerontopsychiatric ward of a university hospital in Germany. To this aim, medication charts of 92 patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Patients' medications comprised a median of eight drugs (IQR 6–11 drugs; range 1–21 drugs). Disease characteristics of the study population have been reported elsewhere 11 . In brief, the three most frequent psychiatric diagnoses in the study population (on the level of n = 92 individual patients) were dementia (39.1%; 36/92), depression (37.0%; 34/92), and schizophrenia/schizophreniform disorder (18.5%; 17/92).…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Patients' medications comprised a median of eight drugs (IQR 6–11 drugs; range 1–21 drugs). Disease characteristics of the study population have been reported elsewhere 11 . In brief, the three most frequent psychiatric diagnoses in the study population (on the level of n = 92 individual patients) were dementia (39.1%; 36/92), depression (37.0%; 34/92), and schizophrenia/schizophreniform disorder (18.5%; 17/92).…”
Section: Resultsmentioning
confidence: 97%
“…Thus, the study populations of Ref. 11 and the present study are essentially the same. Analogous to Ref.…”
Section: Methodsmentioning
confidence: 89%
See 3 more Smart Citations